Identity and history of the Kurdish people and its reflection in the magazine Alai Islam (1986_1998) - Ahmed, Dr. Zhilwan Abdullah (Sulaimani Journal for Humanities, 2025)
Between 1986 and 1998, Alai Islam was published as a cultural and political magazine by the Kurdish Muslim Students Organization Abroad in Canada It had an Islamic intellectual background, which was reflected in the magazine, but it also contained various historical and political articles, especially about the Kurdish people's national liberation movement, which is worthy of mention The magazine also includes several studies on the stages of Kurdish history and the preservation of Kurdish identity. The question of our research is his views What is the attitude of this magazine, published by a Kurdish organization with Islamic ideology, towards Kurdish identity and history? How have they worked to preserve Kurdish identity? We aim to answer this question in this study, so we read all the historical articles of the journal, so that we can answer this question. The paper consists of an introduction, four themes and conclusions. The first topic is a brief history of the magazine, its publication place and the people who supervised it. The second topic is the identity and history of the Kurdish people in the magazine Alai Islam, in which we mentioned his views The third topic discusses the importance of historical writing of the Kurdish people's liberation movement in the magazine Alai Islam, and the fourth topic refers to the situation in Kurdistan At the end of the study, we have mentioned the sources and the results we have reached in the study.
Keywords: Identity; Nationality; History; Flag of Islam; Kurd